The pilgrim's guide to Santiago de Compostela - Melczer, William (Italica Press, 1993)
The Pilgrim's Guide to Santiago de Compostela presents the first complete English translation of Book Five of the Liber Sancti Jacobi or Codex Calixtinus. The Medieval Christian world knew three major pilgrimage sites: Jerusalem, Rome, and Santiago de Compostela. Between the 11th and 13th centuries the pilgrimage to Santiago was by far the most popular, undertaken by hundreds of thousands of pilgrims year after year. This 12th-century guidebook traces the route from southern France to Santiago de Compostela in northwestern Spain. William Melczer discusses Relics and Pilgrimage, The Origin of t.